Improving the Quality of Life
IV, 272 p.
Keywords: The book is unique in two distinct ways. First, it focuses on improving quality of life in contrast to other books that have tended to focus more on its conceptualization and assessment. Second, it deals with improving quality of life in a variety of disabled populations, not just one, and includes chapters on people with chronic mental or physical conditions and those without disabilities at all (i.e. so-called normal people). The book outlines some of the challenges and controversies in the quality-of-life domain and attempts to synthesize the key issue and to draw generalizable conclusions. The book is mainly for university students and faculty and practitioners from various disciplines working in the field. It will also interest those members of the general public who wish to improve their own quality of life or that of their relatives or friends.